What Motivates Successful Marathon Runners? The Role of Sex, Age, Education, and Training Experience in Polish Runners - Waśkiewicz, Zbigniew; Nikolaidis, Pantelis T.; Gerasimuk, Dagmara; Borysiuk, Zbigniew; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2019)
The aim of this study was to compare the motivations of successful marathon finishers (n=1,243) and inexperienced runners (control group, n=296). A total of 1,537 runners with 380 women (24.7%) and 1,157 men (75.3%) completed the Motivations of Marathoners Scales (MOMS) questionnaire, and the relationships between general motivation categories and selected demographic (e.g. gender, age, and education) and training characteristics were analyzed. Successful marathon finishers did not differ significantly in motivations from the control group (p > 0.05). Trivial to small correlations with age, educational level, and training characteristics were observed. Women marathon finishers exceeded men on the motivational scales for weight concern, affiliation, psychological coping, life meaning, and self-esteem and they scored lower on competitive motivation (p < 0.05). These findings confirmed that age and gender differentiate motivations in both successful marathon finishers and controls. There was also a significant relationship of some motivational aspects with level of education, experience and training frequency.